A Four-Year Hospital Journey for a Lost and Migrating Appendicolith. (4th August 2015) - Schraffl, Daniel; Frima, Herman; Villiger, P.
Abstract : We report a rare case of recurrent abscess formation, including being at a retroperitoneal site, due to a lost and migrating appendicolith. Over a four-year period and following an episode of perforated appendicitis, an otherwise healthy young man underwent two operations for abscess formation with eventual stone removal. Appendicoliths can pose a challenge during the diagnostic and therapeutic journey, and adequate attempts at removal need to be made to prevent avoidable complications. In patients suffering from recurrent flank pain and abscesses after appendectomy, the possibility of a lost or overlooked appendicolith should be considered.